Spatial resilience and population replacement in Europe during MIS 3: a comparative study of Neanderthals and H. sapiens - Ariane Burke; Emma Pomeroy; Timothée Poisot; Benjamin Albouy; Simon Paquin (Quaternary Science Reviews, 2026)

Sea, sickness and cautionary tales: a multi-isotope study from a post-mediaeval hospital at the city-port of Gibraltar (AD 1462–1704) - Emma Lightfoot; Emma Pomeroy; Jennifer Grant; Tamsin C. O’Connell; Petrus le Roux; Sonia Zakrzewski; Sarah Inskip; Sam Benady; Clive Finlayson; Geraldine Finlayson; Kevin Lane (Archaeological and Anthropological Sciences, 2020)
During the sixteenth to eighteenth centuries, Spanish ships sailed around the globe connecting Spain to its colonies. While documentary records offer rich details concerning life on board ship, archaeological information is essential to generating a full picture of the past. The cemetery at Old St Bernard’s Hospital, Gibraltar, provides an opportunity to study the skeletal remains of sailors. Following previous osteological research, carbon, nitrogen, oxygen and strontium isotope analyses were undertaken on thirty-three of these individuals. The results show that the, largely male, individuals had various different diets during life and came from several different places. Diets were largely based on C 3 food chains; some individuals consumed C 3 foods with low δ 13 C values; others consumed some marine foods, and a few individuals had a high trophic level diet, through the consumption of either freshwater resources or a high proportion of animal protein. The individuals spent their childhoods in several different places, although these homelands do not correlate simply with dietary variation. This variety in diets and homelands is consistent with our expectations for this hospital site given its location in a post-mediaeval entrepôt. The interpretation of these results are greatly helped by the available historical information and this has broader implications for the interpretation of isotope data elsewhere where the historical context of the site and the mobility patterns of the individuals are less well known.

Estimating body mass and composition from proximal femur dimensions using dual energy x-ray absorptiometry - Emma Pomeroy; Veena Mushrif-Tripathy; Bharati Kulkarni; Sanjay Kinra; Jay T. Stock; Tim J. Cole; Meghan K. Shirley; Jonathan C. K. Wells (Archaeological and Anthropological Sciences, 2019)